FORMULATION OPTIMIZATION AND EVALUATION OF MOUTH DISSOLVING FILM OF RAMOSETRON HYDROCHLORIDE - PATEL, ZANKAHANA; BHURA, RAHIL; SHAH, SAMIR (International Journal of Current Pharmaceutical Research, 2020)
Objective: Ramosetron Hydrochloride is found to be more potent and having a longer duration of action with the least side effects, but the major drawback is it undergoes hepatic first-pass metabolism so our aim is to prepare mouth dissolving film (MDF) of Ramosetron hydrochloride for rapid relief in emesis. Methods: The mouth dissolving films of Ramosetron Hydrochloride were prepared by using the solvent casting method. Films were formulated using HPMC E5 (Hydroxy Propyl Methyl Cellulose) as a film-forming agent, PEG400 (Polyethylene glycol) as a plasticizer and Aspartame as the sweetening agent. A 32 full factorial design was applied considering the concentration of HPMC E5 (X1) and concentration of PEG400 (X2) as independent variables and % cumulative drug release (Y1) (CDR), disintegration time (Y2) (DT) and tensile strength (Y3) (TS) as dependent variables. The prepared films were evaluated for thickness, folding endurance, tensile strength, disintegration time, drug content uniformity and taste masking by E-tongue. The results indicated that factors X1 and X2 were found to be having a positive effect on DT and TS and negative effects on CDR. Results: The optimized formulation was found to be the best with 94.00±0.85% in vitro drug release, 33.22±0.75 sec DT and 1.359±0.005 g/mm2 tensile strength. Concentration of aspartame was optimized with E-tongue taking into consideration increased electric potential with decreasing bitterness. Conclusion: Thus, a rapidly dissolving oral film of Ramosetron Hydrochloride with successful taste masking and immediate in vitro drug release was prepared using a solvent casting technique.